Investor Roles, Green Innovation, and Sustainable Tourism in Mandalika Special Economic Zone - Bagas Anggara; Susilo Talidobel; Rizky Sumardani; Muhammad Taufik; Ni Putu Adya Laksmiamrita; Rianto Rianto (Centre of Excellence in Tourism Udayana University, 2026)
Sustainable tourism has become a strategic priority in Indonesia, particularly in Special Economic Zones such as the Mandalika Special Economic Zone, where economic development must be balanced with environmental and social sustainability. This study examines the influence of investor roles and green innovation on sustainable tourism development. A mixed-methods sequential explanatory design was employed. The quantitative phase involved a survey of 100 tourism investors across accommodation, restaurant, and tour and travel sectors, analyzed using SmartPLS. This was followed by a qualitative phase consisting of interviews, observations, and focus group discussions with 25 stakeholders, including government representatives, industry actors, and local communities. The results indicate that both investor roles and green innovation have significant positive effects on sustainable tourism (Investor Role: β = 0.385, p < 0.001; Green Innovation: β = 0.281, p < 0.001), with an R² value of 0.575. These findings suggest that investor engagement and the adoption of environmentally oriented innovations contribute substantially to explaining variations in sustainable tourism performance. Qualitative findings further reveal that sustainable tourism development is supported by the alignment of investor activities, policy frameworks, and community participation, particularly in economic contribution, resource efficiency, and environmental practices.This study contributes to the empirical understanding of how investment and innovation interact in shaping sustainable tourism outcomes in emerging destinations.